PRINCIPAL ON DUTY IN THE COVID ERA - Hanisah, Kasbon; Farah Liyana, Ahmad Azmey (Pusat Bahasa Moden (PBM), 2021)
One of our CML colleagues, Puan Rosjuliana Hidayu binti Rosli, a senior language teacher is no stranger to Residensi Pelajar 3 or better known as KK3. Going into her fifth-year of principalship, year 2020 completely changed the college living landscape. While the year was prepared with a lot of plans, the global pandemic has broken and shattered everything at one go.